(untitled) (Religious dialogue and cooperation, 2021)
Poland and Poles are and have always been strongly attached to Catholicism. In the national tradition, we define ourselves as the „rampart (defensive wall) of Christianity,” securing Europe from the dominance of Islam (the Ottoman Empire). During the partition period, confession was the determinant of being a Pole. The Catholic Church was perceived as a mainstay of Polish national identity, the only institution where Polish language could be used. The church was similarly treated during the communist period, as well - it was the mainstay of patriotism, helped the illegal opposition, organized help for the persecuted. No wonder that in the traditional social narrative the church was and still is treated as a national institution, and confession as an important (even dominant) component of national identity. Being a Catholic was a source of pride, after all we had the Polish Pope. Why, then, the thesis that it is at a crossroads? I assume that it is determined by the present conditions and processes that take place on a global scale. Poland, which has been surprised by full churches, currently has the largest decline in dominicantes and communicantes in the whole world, despite the fact that most of the Poles declare themselves to be Catholics. What decides about it? In my opinion, approaching Catholicism and its practices as a shelf in a supermarket - one chooses what is useful to him at a given moment. There is also another aspect of Church activity in Poland - political activity that expresses support for those parties that appeal to nationalism, traditional narrative to the role of the Church in the past and influencing the creation of the law, that religious dogmas/norms (Catholic) should be respected. This testifies to the weakness of the evangelizing and educational mission of the Church. Keywords: Catholic